Efeitos da deficiência de vitamina D na função pulmonar de um modelo de asma alérgica experimental - Nuñez, Nailê Karine (2017)
Background: Asthma is a chronic disease of the airways, characterized by bronchial inflammation and hyperresponsiveness, which affects approximately 300 million people around the world. The increase in the prevalence of asthma in recent years has been associated with an increase in vitamin D deficiency. About 1 billion people in the world have insufficient levels of vitamin D due to many factors such as reduced outdoor activities, sunscreens use and a diet low in vitamin D. In addition, many studies suggest that vitamin D deficiency has a direct effect on lung function, leading to changes in the structure of the airways and in the inflammatory process. Objectives: To evaluate the effect of vitamin D deficiency at different life stages in a murine model of allergic airways disease house dust mite (HDM) induced on inflammation and lung function. Methods: Female BALB / c mice were placed in a diet replete or deficient in vitamin D at three-week old. At 8 weeks, females were mated with males on a diet replete in vitamin D. At birth, pups were cross-fostered to assess the effects of vitamin D deficiency at different stages of life, in utero (Vit D -/+), postnatal (Vit D +/-) and whole-life (Vit D - / -) compared to the control group whole-life vitamin D replete (Vit D + / +). At 8 weeks of age, mice of both sexes were challenged for 10 consecutive days intranasally with either HDM extract or saline solution after mild anesthesia. The animals were anesthetized for lung function test and then submitted to euthanasia for bronchoalveolar lavage (BAL) and lung tissue removal 24 hours after the last intranasal challenge. The total BAL cell count and collagen quantification of lung tissue homogenized were evaluated. Results: Vitamin D deficiency did not affect HDM-induced inflammation, which was characterized by BAL eosinophilia. Vitamin D deficiency at any life stage (in utero, postnatal and all life) caused impairment of lung function, increased tissue damping and tissue elastance, being particularly observed in females. On the other hand, the asthma HDM-induced decreased airway distensibility, but only in females and vitamin D do not altered this response. Conclusion: Our results suggest that vitamin D and HDM have different mechanisms that influence in the development of allergic lung disease and furthermore the effects appear to be sex-specific.